La médiation culturelle pour les sourds dans le milieu muséal au Québec - Ingrid Valent (Conserveries Mémorielles)
Through this paper, we propose an exploration of the cultural mediation related to the deaf community. Despite all improvements of devices in cultural mediation in museal context, there is still populations who don’t visit, or not much, museums. Also, it would be a reflexion about the difficulties encounter by the deaf population on their access in cultural museums with an analysis of three thematic : the particular needs of this community ; the mediation devices who existed in Quebec and those who would be implanted ; without forgotten some elements who would be considered as hints. This research is developed as a qualitative exploratory survey and its topics will enable to clarify a matter not much developed and to delimit its specifics. The goal of this paper would be to realize the differences within museum publics and to sensitize about the needs of a global accessibility in terms of owns public characteristics.